2021
DOI: 10.1038/s41467-020-20449-w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle delivery of microRNA-146a regulates mechanotransduction in lung macrophages and mitigates injury during mechanical ventilation

Abstract: Mechanical ventilation generates injurious forces that exacerbate lung injury. These forces disrupt lung barrier integrity, trigger proinflammatory mediator release, and differentially regulate genes and non-coding oligonucleotides including microRNAs. In this study, we identify miR-146a as a mechanosensitive microRNA in alveolar macrophages that has therapeutic potential to mitigate lung injury during mechanical ventilation. We use humanized in-vitro systems, mouse models, and biospecimens from patients to el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…Amongst the recruited immune cells, PMN appears always to be recruited at a higher amount with ventilation. Bobba et al have shown that PMNs are mechanosensitive, and they release cytokines in response to barotrauma, increased pressure usually associated with mechanical ventilation that causes alveolar damage [29]. The presence of PMN with mechanical ventilation correlate to our data where there was a high rise of PMN with ventilation in both young and old group.…”
Section: Damage Due To MVsupporting
confidence: 87%
“…Amongst the recruited immune cells, PMN appears always to be recruited at a higher amount with ventilation. Bobba et al have shown that PMNs are mechanosensitive, and they release cytokines in response to barotrauma, increased pressure usually associated with mechanical ventilation that causes alveolar damage [29]. The presence of PMN with mechanical ventilation correlate to our data where there was a high rise of PMN with ventilation in both young and old group.…”
Section: Damage Due To MVsupporting
confidence: 87%
“…Unfortunately, there have been no other therapeutic options that have proven uniformly effective or have been approved for the treatment of ARDS in humans, whether due to VILI or other etiologies. Therapeutic modalities that have been proposed for treatment of VILI based on animal studies include the cholesterol-lowering agent simvastatin [32], the inhaled anesthetic sevoflurane [54], bixin to target NRF2 [55], neuromuscular blocking agents to reduce ventilator-patient asynchrony [56], H 2 S to regulate ER stress [57], microRNA 146a for altered mechanotransduction [58], dexmedetomidine to activate ERK 1,2 [59], alpha1-antitrypsin to inhibit neutrophil elastase [19], and various anti-inflammatory agents including ginsenoside [12] and lipoxin A4 [60], but none of these agents or procedures has been approved for use in the ICU. Based on the mouse studies of acute lung injury, PIP-2 represents a potential therapeutic agent for treating or preventing VILI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts have begun exploring therapeutic opportunities (e.g. gene delivery) to mitigate lung injury in the deep alveolar regions 13 . Still, it remains widely unknown to what extent mechanical forces influence the downstream precursors leading to biotrauma.…”
Section: Introductionmentioning
confidence: 99%